Canadian content at GU-ASCO 2014: Highlights of research involving Canadian researchers - Kapoor, Anil (Canadian Medical Association, 2014)
The 2014 Genitourinary Cancers Symposium (GU-ASCO 2014) provided an opportunity for researchers from around the world to present their research in a variety of fields, including prostate, renal cell, penile, urethral and testicular cancers. Over the symposium’s 3 days, Canadian researchers were well-represented, with a number of oral abstract podium presentations and many more research posters. The following section provides brief summaries of some of the most interesting work involving Canadians presented at GU-ASCO 2014 and a listing of all the studies that included contributions from Canadian researchers.